Penggunaan Buku Cerita Digital untuk Mengenalkan Mitigasi Bencana Kebakaran Bagi Anak Usia Dini - Mauludiyah, Fajar; Nurani, Yuliani; Hikmah, Hikmah (Indonesian Journal Publisher, 2024)
The research is about to develop digital storytelling media in introducing fire disaster mitigation for children aged 5 to 6. This research uses the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). This research method was using questionnaire instruments for expert review and evaluation instruments one to one for children aged 5 – 6 years. The results of the validity test of the product by the material expert obtained a hard score of 100%. The product validity testing results by the media expert received a final score of 77.5%. The validity tests of practitioners or teachers at the PAUD Institute obtaining a value of 97.5%. Product effectiveness test results in children aged 5 – 6 years gave a final value of 80.1%. Research results showed that the digital storytelling books qualified. The digital storytelling media has been successful in introducing fire disaster mitigation to children aged 5-6 years. This book can provide an introduction to the dangers of playing with flammable objects, objects that can extinguish fires, and actions taken in the event of a fire. This book can be practically used as a learning medium by children with the support and guidance of teachers and parents.